Negotiations and love songs Heloise and the question of religious authenticity - Chua, Sharon Jane Go (ProQuest LLC, 2009)
The letters of Abelard and Heloise have mostly been analyzed and critiqued via the artificial dichotomy of "personal" and "instructional," resulting in a static and monolithic account of Heloise's so-called transgressive desires. This thesis argues, however, that the letters by Abelard and Heloise, together with their liturgical works for the Oratory of the Paraclete, constitute an ongoing negotiation for the redefinition of authenticity within the religious life. Heloise's unflinching devotion to her ideal of love becomes her primary impetus for challenging the blind adherence to St. Benedict's Rule that was pervasive in twelfth century religious devotion.--Abstract.